La population des villes sudarabiques préislamiques : entre ‘aṣabiyya et ḥaḍarî - Jérémie Schiettecatte (Revue des Mondes Musulmans et de la Méditerranée)
The identity of the pre-Islamic populations of South Arabia is signified by way of the available epigraphic data. These data have provided a perspective into the way in which urban populations identified themselves. At the outset (8th–2nd c. B.C.), these populations defined themselves by a link to parentage. Conversely, at the turn of the Christian era throughout South Arabia, identity is progressively expressed by an association with the city of origin, or to place. This chronological evolution brings us to relativize the ancient dichotomy through which the identity of highland populations is defined as an affiliation to place while that of the populations of the lowlands is defined as an association to blood or heredity.Alternatively, this evolution appears to go hand in hand with a profound societal transformation whereby the tie to ancestry gives way to new forms of hierarchy in relationships of dominance and of the appropriation of resources. Such a socio-economic transformation may well have provided the impetus for this evolution of the identity of urban South Arabian populations.